(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2018)
This article discusses recent works on the notions of postpolitics and sustainability in conjunction with illustrative examples from empirical data collected during long-term fieldwork in and around the tourist town of Broome in the West Kimberley region in Australia. I argue that for policy research and practice to remain a significant contributor to contemporary research on sustainability in the Anthropocene, it needs to develop more collaborative approaches that cater to the involvement of numerous and diverse actors in decision-making processes. The article outlines some of the methodological challenges this poses, and how to address them.